2020
DOI: 10.1038/s41598-020-68162-4
|View full text |Cite
|
Sign up to set email alerts
|

The effect of Cu nanoparticle adding on to epoxy-based adhesive and adhesion properties

Abstract: Epoxy-based adhesives are widely used for repairing or jointing the metal sheets in the industry. Because of their superior mechanical properties, the metallic nanoparticles can be selected as the additive of the epoxy adhesive. The strength of the Cu nanoparticles (CuNPs) can be expected to improve the mechanical properties of neat epoxy. In this study, CuNPs were added at various weight ratios, such as 1, 2, 5, 10, 15, and 20% into the epoxy resin adhesive. Tensile tests of the dog-bone specimens and the lap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…Moreover, the adhesive strength obtained by heat-curing the adhesive at 130 • C is higher than that achieved by curing at 120 • C. The adhesion strength of the adhesive containing 0.5 wt% of PMMA/PEI cured at 130 • C is 27.5 kgf cm −2 , which is higher than that of an adhesive with the same concentration cured at 120 • C. Moreover, when the concentration of PMMA/PEI nanoparticles increases to 1.0 and 1.5 wt%, the adhesive strength increases to 34.7 and 40.2 kgf cm −2 , respectively. This result is attributed to the dual effect of high curing temperature, which is close to the T g of the resin and the presence of numerous crosslinking sites between the epoxy resin and amine groups of nanoparticles [21][22][23]. Notably, the maximum adhesion strength of the new adhesive using the proposed PMMA/PEI nanoparticles was 352% higher than that of conventional adhesive.…”
Section: Adhesive Strength and Elongation Property Of New Uv/heat Duamentioning
confidence: 88%
“…Moreover, the adhesive strength obtained by heat-curing the adhesive at 130 • C is higher than that achieved by curing at 120 • C. The adhesion strength of the adhesive containing 0.5 wt% of PMMA/PEI cured at 130 • C is 27.5 kgf cm −2 , which is higher than that of an adhesive with the same concentration cured at 120 • C. Moreover, when the concentration of PMMA/PEI nanoparticles increases to 1.0 and 1.5 wt%, the adhesive strength increases to 34.7 and 40.2 kgf cm −2 , respectively. This result is attributed to the dual effect of high curing temperature, which is close to the T g of the resin and the presence of numerous crosslinking sites between the epoxy resin and amine groups of nanoparticles [21][22][23]. Notably, the maximum adhesion strength of the new adhesive using the proposed PMMA/PEI nanoparticles was 352% higher than that of conventional adhesive.…”
Section: Adhesive Strength and Elongation Property Of New Uv/heat Duamentioning
confidence: 88%
“…Necati Ataberk [26] reported that the strength of the adhesive and the strength of the joint is the different characteristics of an adhesive material. Maximum tensile strength (96.34 MPa) of the bulk specimen was obtained for 15 wt% Cu nano-particle added specimen, but the maximum joint strength (15.52 MPa) was obtained for 10% Cu nanoparticle added specimen.…”
Section: Nano Silver (Ag)mentioning
confidence: 99%
“…However, the type of preferred interaction and filler morphology on the dispersion are still undetermined. The dispersion of silica nanoparticles were found to be enhanced when ethylene glycol groups are attached to its surface [22] [23]. In the case of thermosets there are a lot of considerations especially in incorporating nanomaterials to the liquid matrix as it requires proper dispersion and exfoliation.…”
Section: Introductionmentioning
confidence: 99%